1988
DOI: 10.1177/039139888801100312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Membrane Trapping in Plasma Fractionator on Separative Characteristics

Abstract: Several kinds of plasma fractionators have been introduced to actively separate protein fractions between albumin and globulins in double filtration plasmapheresis. However, relatively large molecular weight proteins are known to be partially trapped by the membrane in a plasma fractionator. In this paper, effects of membrane trapping on separation characteristics in plasma fractionators were examined during in vitro and in vivo studies. All in vitro experiments were done with a closed circuit under constant-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…This was similar to the results of an increase in SC of fibrinogen using the DF Thermo method with an Evaflux‐5A plasma fractionator until the PPV was 3.0 L . Usually, SC of proteins in the membrane separator decreases after the treatment is initiated . In the present study, if the PPV had been much higher, SC of fibrinogen may have started to decrease, similar to the previous study .…”
Section: Discussionsupporting
confidence: 91%
“…This was similar to the results of an increase in SC of fibrinogen using the DF Thermo method with an Evaflux‐5A plasma fractionator until the PPV was 3.0 L . Usually, SC of proteins in the membrane separator decreases after the treatment is initiated . In the present study, if the PPV had been much higher, SC of fibrinogen may have started to decrease, similar to the previous study .…”
Section: Discussionsupporting
confidence: 91%
“…FH is characterized by the accumulation of VLDL/LDL particles in the blood because of genetic dysfunction of LDLR or LDLR-related genes 15 . Therefore, lipoprotein apheresis treatment is important to prevent the onset of atherosclerosis and cardiovascular disease in patients with FH 1619 . Lipoprotein apheresis treatment can selectively remove VLDL/LDL cholesterol from blood through the electrostatic interaction of dextran sulfate in the lipoprotein apheresis column with apoB on (V)LDL particles 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Lipoprotein apheresis treatment is vital to FH patients because the presence of abnormally high LDL cholesterol leads to the formation of atherosclerotic plaques and increases the risk of cardiovascular diseases 1619 . Lipoprotein apheresis treatment is currently believed to selectively eliminate VLDL/LDL cholesterol 20 .…”
Section: Discussionmentioning
confidence: 99%
“…DeGenne et al conducted plasma exchange (PE) in homozygous FH patients in 1967 (3), and in 1975 Thompson et al reported the LDL-C-reducing effects of PE on the alleviation of angina pain with the improvement of coronary artery stenosis (4). Subsequently, attempts to remove LDL in more selective ways have been made by using a special double-filtration plasmapheresis (DFPP) method termed thermofiltration (5)(6)(7) and an LDL adsorption column (8,9). Collectively, these two methods have been called LDL-apheresis (LDL-A).…”
mentioning
confidence: 99%